Women's Access to Land and Decision-Making in Rice Production and Social Reproduction in Rural Philippines - Lumayag, Linda Alfarero (1992)
Some studies generally argued that in rice-based farming communities women's access to land enhances their ability to influence men in decision-making in the rice production process and in social reproduction (income allocation) in the households. This study was basically an attempt to decipher the gender relations between husband and wife and sought to provide a tentative analysis of the position of Filipino women in the household and in the community. Generally, this study examined the relationship between women's access to land as owners and tenants and their influence in decision-making in rice production and social reproduction. In particular, it tried to determine the extent of women's access to land and the factors which promote or inhibit such access; to determine whether the different tenurial statuses of women land owners and tenants have varying degrees of influence in decision-making in production and social reproduction; to determine the involvement of women and their changing role in rice production; and to examine the degree of women's influence in social reproduction.